DIGITAL ECONOMY STANDARDS IN DISTANCE EDUCATION DEVELOPMENT: CURRENT STATE AND TRENDS (International scientific-electronic journal “Pioneering studies and theories”, 2026)
The rapid expansion of the digital economy has fundamentally transformed the structure and organization of distance education worldwide. The increasing role of international standards in digital infrastructure, data governance, interoperability, cybersecurity, and quality assurance has created new regulatory and methodological frameworks for the development of online and blended learning systems. In this context, a systematic analysis of global digital economy standards and their influence on distance education becomes essential for understanding current transformation processes and identifying emerging development trajectories.This review article examines the current state and evolving trends of distance education development through the prism of global digital economy standards. The study synthesizes international regulatory frameworks, policy documents, and academic research related to digital education, EdTech platforms, learning management systems, and cross-border educational services. Particular attention is paid to standards formulated by international organizations such as the OECD, UNESCO, ISO, the European Union, and the World Bank, which shape institutional models, technological architectures, and quality assurance mechanisms in digital learning environments.The analysis identifies key standardization domains, including digital infrastructure, data protection, interoperability of educational platforms, digital credentials, and competency frameworks for the digital workforce. The review further highlights emerging trends such as platformization of education, internationalization of online programs, integration of artificial intelligence and learning analytics, and the growing role of transnational regulatory coordination. The findings reveal that alignment with global digital economy standards plays a decisive role in enhancing the scalability, quality, and international compatibility of distance education systems.
Keywords: digital economy standards; distance education; global standardization; online learning systems; digital infrastructure; quality assurance; international integration; EdTech platforms; cross-border education